Are strict vegetarians protected against prostate cancer?. Issue 1 (11th November 2015) - Tantamango-Bartley, Yessenia; Knutsen, Synnove F; Knutsen, Raymond; Jacobsen, Bjarne K; Fan, Jing; Beeson, W Lawrence; Sabate, Joan; Hadley, David; Jaceldo-Siegl, Karen; Penniecook, Jason; Herring, Patti; Butler, Terry; et al.
ABSTRACT: Background: According to the American Cancer Society, prostate cancer accounts for ∼27% of all incident cancer cases among men and is the second most common (noncutaneous) cancer among men. The relation between diet and prostate cancer is still unclear. Because people do not consume individual foods but rather foods in combination, the assessment of dietary patterns may offer valuable information when determining associations between diet and prostate cancer risk. Objective: This study aimed to examine the association between dietary patterns (nonvegetarian, lacto-ovo-vegetarian, pesco-vegetarian, vegan, and semi-vegetarian) and prostate cancer incidence among 26, 346 male participants of the Adventist Health Study-2. Design: In this prospective cohort study, cancer cases were identified by matching to cancer registries. Cox proportional hazards regression analysis was performed to estimate HRs by using age as the time variable. Results: In total, 1079 incident prostate cancer cases were identified. Around 8% of the study population reported adherence to the vegan diet. Vegan diets showed a statistically significant protective association with prostate cancer risk (HR: 0.65; 95% CI: 0.49, 0.85). After stratifying by race, the statistically significant association with a vegan diet remained only for the whites (HR: 0.63; 95% CI: 0.46, 0.86), but the multivariate HR for black vegans showed a similar but nonsignificant point estimate (HR: 0.69; 95% CI: 0.41, 1.18). Conclusion: Vegan diets may confer a lower risk of prostate cancer. This lower estimated risk is seen in both white and black vegan subjects, although in the latter, the CI is wider and includes the null.